Telecom-operators cryptography application system with quantum key distribution - Jun LUO; Chi LIU; Binglei WANG (Dianxin kexue)
The communication network based on quantum key distribution (QKD) has the ability to realize “perfect secrecy”.At present, it cannot meet the needs of large-scale applications and needs to combine classical cryptography in practical applications.Firstly, the functional architecture model of the telecom-operators cryptography application system integrating quantum key distribution was proposed, and then the hierarchy, the core network elements, the functional modules, and the interface relationships of the model were described.Furthermore, the framework of the application system was given, and the main components of the framework were introduced.Finally, the typical application scenarios and workflow were illustrated.